Capacity gaps in health facilities for case management of intestinal schistosomiasis and soil-transmitted helminthiasis in Burundi - Bizimana, Paul (Infect Dis Poverty, 2018)
BACKGROUND: Schistosomiasis and soil-transmitted helminthiasis (STH) are endemic diseases in Burundi. STH control is integrated into health facilities (HF) across the country, but schistosomiasis control is not. The present study aimed to assess the capacity of HF for integrating intestinal schistosomiasis case management into their routine activities. In addition, the current capacity for HF-based STH case management was evaluated. METHODS: A random cluster survey was carried out in July 2014, in 65 HF located in Schistosoma mansoni and STH endemic areas. Data were collected by semi-quantitative questionnaires. Staff with different functions at the HF were interviewed (managers, care providers, heads of laboratory and pharmacy and data clerks). Data pertaining to knowledge of intestinal schistosomiasis and STH symptoms, human and material resources and availability and costs of diagnostic tests and treatment were collected. FINDINGS: Less than half of the 65 care providers mentioned one or more major symptoms of intestinal schistosomiasis (abdominal pain 43.1%, bloody diarrhoea 13.9% and bloody stool 7.7%). Few staff members (15.7%) received higher education, and less than 10% were trained in-job on intestinal schistosomiasis case management. Clinical guidelines and laboratory protocols for intestinal schistosomiasis diagnosis and treatment were available in one third of the HF. Diagnosis was performed by direct smear only. Praziquantel was not available in any of the HF. The results for STH were similar, except that major symptoms were more known and cited (abdominal pain 69.2% and diarrhoea 60%). Clinical guidelines were available in 61.5% of HF, and albendazole or mebendazole was available in all HF. CONCLUSIONS: The current capacity of HF for intestinal schistosomiasis and STH detection and management is inadequate. Treatment was not available for schistosomiasis. These issues need to be addressed to create an enabling environment for successful integration of intestinal schistosomiasis and STH case management into HF routine activities in Burundi for better control of these diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40249-018-0447-y) contains supplementary material, which is available to authorized users.